Status of the draft potato ontology. - Simon, R.; Bonierbale, Merideth W. (2013)
The potato ontology is being developed as part of the crop ontology (CO) effort amongst CGIAR centers. The CO serves primarily to harmonize phenotypic and genotypic data for semantic compatibility across diverse, distributed data types; and ontology in general, facilitates the use of terms by both humans and algorithms. Other potential uses include knowledge transfer across species and predictions. The case of potato presents several opportunities to test and evaluate the different uses of ontologies: a) potato has more than 100 tuber-bearing wild relatives, b) the potato genome and that of its sister species, tomato, have recently been sequenced, and c) conserved orthologous set (COS) gene sequences markers have been mapped in the physical and genetic map of potato and tomato. On the other hand potential constraints are: a) potato is outbreeding and has a high level of diversity at genotype and phenotype level; and b) predictivity of transferring knowledge between species has been weak in the past. In this talk we will present main advances and pendings to date around the use of the potato ontology. These include: a) development of a first potato ontology based on the former FAO/IPGRI/CIP morphological descriptor list and trait dictionaries from standard evaluation trial protocols; b) the P4 initiative open to collaborators for phenotyping and gene discovery from the DMDD progeny of the sequenced genome, DM ,and c) a federated web database using biomart for integrating genome scale and field trial data. Current efforts include the addition and standardization of new phenotypes, as well as improving the ontology draft in terms of coverage of data types and cross linking to the general plant as well as to the Solanaceae Phenotype Ontology.